Biography and history teaching. A didactic proposal for its approach in Santa Fe middle schools based on two life trajectories (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2021)
In the article we present to the reader a didactic proposal based on the importance of thinking about the potential of biography in the teaching of the discipline. From this approach, we explore two life stories, that of a man and a woman -Juan Canals and Dolores Cobo-, belonging to the highest sectors of Santa Fe society during the agro-export boom, with the purpose of approaching some of the curricular contents corresponding to the secondary level of the province of Santa Fe. Through the analysis of certain problems that run through both biographies, we recovered a set of inputs and feasible activities to work on certain issues of Local/Regional History in the classroom.
Keywords: Historical Biography; Regional History; Local History; teaching